Wnt Activity and Cell Proliferation Are Coupled to Extracellular Vesicle Release in Multiple Organoid Models - Gyöngyvér Orsolya Sándor; András Áron Soós; Péter Lörincz; Péter Lörincz; Lívia Rojkó; Tünde Harkó; Levente Bogyó; Levente Bogyó; Tamás Tölgyes; Attila Bursics; Edit I. Buzás; Edit I. Buzás; et al. (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EV) are considered as a potential tool for early disease diagnosis; however, factors modifying EV release remain partially unknown. By using patient-derived organoids that capture the cellular heterogeneity of epithelial tissues, here we studied the connection between the Wnt-producing microniche and EV secretion in multiple tissues. Although nearly all cells in pancreatic ductal (PD) and pancreatic ductal adenocarcinoma (PDAC) samples expressed porcupine (PORCN), an enzyme critical for Wnt secretion, only a subpopulation of lung bronchiolar (NL) and lung adenocarcinoma (LUAD) organoid cells produced active Wnt. The microniche for proliferating cells was shaped not only by PORCN + cells in NL and LUAD organoids but also by fibroblast-derived EVs. This effect could be blocked by using Wnt secretion inhibitors. Whereas inhibiting Wnt secretion in PD NL or LUAD organoids critically changed both cell proliferation and EV release, these were uncoupled from each other in PDAC. Sorting for CD133 identified a cell population in the LUAD microniche that produced organoids with a high percentage of PORCN + and proliferating cells and an elevated EV secretion, which may explain that CD133 marks LUAD cells with malignant behavior. Collectively, we show here that high cell proliferation rate, induced by Wnt pathway activation, is coupled to a higher EV release, a critical finding that may be considered when developing EV-based diagnostic tools.